Anogenital index and bone mineral density associations after natural and surgical menopause: a preliminary study - Buyuk,Gul Nihal (2022)
SUMMARY OBJECTIVE: The aim of this study was to evaluate postmenopausal women to determine whether an anogenital index (AGI) is associated with bone mineral density (BMD) based on the hypothesis that the effects of menopause are similar for both. METHODS: A total of 338 generally healthy postmenopausal women who were referred for a routine annual check and 140 women who met the inclusion criteria were enrolled in the study. Based on the menopausal status, the women were classified into natural menopause and surgical menopause. AGI was calculated by dividing anogenital distance by body mass index. The BMD of the femoral neck, body of the femur, and lumbar spine (L1 and L2) was measured using dual-energy x-ray absorptiometry. RESULTS: There was a statistically significant and same-directional correlation between age and AGI for all cases (r=0.234 and p=0.005). The AGI level decreased as the parity increased (r=-0.582 and p<0.001). The AGI level decreased significantly as the menopause duration was prolonged (r=0.288 and p<0.001). While there was no statistically significant correlation between L2-L4 BMD and AGI (p=0.128), as the femur and femoral neck BMD levels increased, the AGI level increased statistically significantly (r=0.330 and p<0.001, r=0.292 and p<0.001). CONCLUSION: The AGI levels in healthy postmenopausal women give preliminary information about their BMD status. A decrease in AGI levels may predict lower BMD in postmenopausal women. Further larger and well-controlled studies may be required to determine the relationship between AGI and BMD in the future.